Flower wastes as a low-cost adsorbent for the removal of acid blue 9 (2014)
This paper describes the use of flower wastes (carnation, rose and daisy) as a potential, alternative and low-cost adsorbent for the removal of Acid Blue 9 (AB9). The best conditions to achieve an efficient adsorption were evaluated in a batch process. With an acidic pH of 2.0, a removal exceeding 90% was obtained using concentrations of AB9 of 15.0 mgL-1 and a dosage of adsorbent of 4.0 gL-1. The equilibrium of the process was modeled using the Langmuir and Freundlich isotherms, obtaining a better fit with the latter one. Kinetic studies indicated a better fit of the process to a pseudo-second order model and negligible effect of temperature. In addition, the bromatological characterization of the adsorbent is shown.